New doping process mode to synthesize in situ N-MWNTs in novel coaxial nanostructure - O. Guellati, F. Antoni, M. Guerioune and D. Bégin (Catalysis Today, 2018)
Nitrogen-doped MWNT “N-MWNT” have gained an increasing interest because particularly of their electronic properties allowing their use in specific applications such as catalysis, sensors, nano-electronics and energy storage. In this investigation, novel coaxial structures consisting of concentric shells of pure carbon MWNT cores with external nitrogen-doped carbon walls (N-MWNT) were produced using a catalytic CVD process, with ethane and ammonia as carbon and nitrogen sources over Fe–Al2O3 support. In order to optimize the growth conditions of such N-MWNT nanostructures, we investigate the influence of different key parameters, i.e., ammonia injection moment in two doping process modes “Instantaneously doping and Mid-doping”, growth temperature (750 and 850 °C) and the presence of H2 as reducer gas in the reaction environment. A strong correlation between ammonia injection duration (60, 90 and 120 min) and nitrogen content (from 0.4 at.% to 2.2 at.%) incorporated in the nanotube products was observed and different coordination between C and/or O atoms have been described by XPS. These functionalized MWNTs were characterized using HR-TEM, FESEM, XPS, BET, TG analyses and Raman spectroscopy in order to determine their structural characteristics (graphitization and crystallinity) in quantitative and qualitative ways.